Isolation, Identification, and Antioxidant Activity of Flavonoid Compounds in the Ethanol Extract in Bandotan Leaves (Ageratum conyzoides) - Siti Mutingatun; Enny Fachriyah; Dewi Kusrini (Jurnal Kimia Sains dan Aplikasi, 2022)
Isolation of flavonoid compounds from the ethanol extract of Bandotan leaves (Ageratum conyzoides L.) has been successfully conducted. The structure of flavonoid isolates was identified using UV-Vis spectrophotometry with the addition of shear reagents and FTIR. In addition, the antioxidant activity of the isolates was determined and studied using the DPPH (2,2-Diphenyl-1-picrylhydrazyl) method. This study aimed to isolate, identify, and test the antioxidant activity of flavonoid compounds from Bandotan leaves. An antioxidant activity test was carried out on ethanol extract, and flavonoid isolates using the DPPH method. Based on this research, Bandotan leaf ethanol extract yielded 13.964%. The results of the phytochemical screening test revealed that the leaf powder and ethanol extract of Bandotan leaves contained alkaloids, flavonoids, saponins, tannins, quinones, steroids, and triterpenoids. The total flavonoid content of the ethanol extract of Bandotan leaves was 129.27 mg EQ/g extract. Identification of flavonoid isolates using a UV-Vis spectrophotometer showed that flavonoid isolates belong to the flavanone compound class with maximum absorption at a wavelength of 315 nm (band I) and 280 nm (band II). FTIR analysis showed that the flavonoid isolates had functional groups O-H, C-H aromatics, C-H alkanes, C=O, C=C aromatics, C-O ethers, C-O alcohols, and substituted aromatic rings. Identification of the structure of flavonoid isolates with a spectrophotometer with the addition of shear reagent and FTIR, presumably that the isolate was a 4’-hydroxy flavanone compound. The antioxidant activity of ethanol extract showed moderate antioxidant activity (IC50 118.19 µg/mL) and was classified as very weak (IC50 1185.5 µg/mL).